Why does 'academic' theology disable ministry?. Issue 4 (4th July 2022) - Heywood, David
ABSTRACT: Dissatisfaction about the 'academic' nature of ministerial training has existed for a considerable time. In a small-scale qualitative study of ministers in the Anglican Diocese of Oxford, England, it emerged that most if not all had experienced a disconnect between their academic study and the realities of ministry and had found the study of academic theology disabling for ministry. This article uses the framework of learning in communities of practice to explore their experience. It concludes that the disconnect stems from the subject-centred nature of theological scholarship in contrast to the life-centred concerns of discipleship and ministry. The interests of academic theologians frequently do not tally with those of ministers and the nature of academic theology differs from that of the 'everyday' theology that forms a component of a Christian social imaginary. The signature pedagogy required for ministerial formation is a pedagogy of theological reflection rather than theological scholarship.